Validation for CFD Simulation in Rod Bundles With Split-Vane Spacer Grids Based on LDA Measurement - Xiong, Jinbiao; Lu, Chuan; Qu, Wenhai (Frontiers in Energy Research, 2020)
Laser Doppler anemometry (LDA) measurement of axial flow velocity and pressure drop measurement has been carried out in a 5x5 rod bundle installed with two split-mixing-vane grids. The measured results are utilized to validate the CFD simulation. The realizable and nonlinear k-ε turbulence model is utilized in the CFD computation, while the two-layer wall treatment is employed with both models. Mesh sensitivity investigation shows that the pressure drop is weakly affected by local mesh refinement in the spacer grid, while its effect on the velocity in the near wake of spacer grid is apparent. The validation shows that prediction on the mean axial velocity is relatively poor in the near wake of the spacer grid where the measured result shows relatively smooth distribution of axial velocity. Refinement of mesh in the spacer grid eliminates some peaks for the nonlinear model. Comparing with the effect of mesh refinement, the difference caused by the turbulence models is relatively weak in the near wake region. In the far-wake region it is still difficult to judge which model shows definite superiority to the other. For pressure drop, prediction of nonlinear k-ε is closer to the experiment.